2022
DOI: 10.32996/jbms.2022.4.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Online Advertisements: Its Impact on Late Generation Z’s Purchase Intention

Abstract: Online advertising is considered as one of the most popular forms of communication in persuading consumers to purchase a product. It asks the question of how an advertisement becomes well-written or well-processed. Correspondingly, many factors contribute to making an online advertisement a successful process. In this light, the researchers aim to determine the influence of the different elements of online advertisements on Late Generation Z's purchase intention. To be more particular, the researchers focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Kizgin et al [5] suggested that Social media has become a powerful instrument for fostering and encouraging relationships between individuals, group of people and businesses to ascertain if suggestions for products made by other users on social networking sites (like Facebook, blogs, and Twitter) can affect consumers' intentions to make a purchase. According to Mergillano et al [6], the most common method of communication for convincing customers to buy a product is online advertising. Also showing that Late Generation Z always values certain aspects of web ads.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kizgin et al [5] suggested that Social media has become a powerful instrument for fostering and encouraging relationships between individuals, group of people and businesses to ascertain if suggestions for products made by other users on social networking sites (like Facebook, blogs, and Twitter) can affect consumers' intentions to make a purchase. According to Mergillano et al [6], the most common method of communication for convincing customers to buy a product is online advertising. Also showing that Late Generation Z always values certain aspects of web ads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They may also include celebrity spokespeople or endorsers to deliver a message 5 ).Your business can notify potential clients about a certain good, service, or deal by using television advertisements to reach them at home. Ads that are memorable to the public 6 .…”
Section: Televsion (Tv)mentioning
confidence: 99%